The Modern Woman's Image in Single’s Inferno 3 - Putri, Astrid Hidayanti Ananda (Journal of Language, Communication, and Tourism, 2024)
Reality dating shows have emerged as an influential genre in global entertainment, shaping and reflecting cultural norms related to relationships, gender, and identity. Single's Inferno 3, a Korean dating reality show, exemplifies this influence, particularly in its reception in Indonesia. Among the contestants, Choi Hye-seon stands out for her confident and authentic persona, challenging traditional archetypes of femininity. Unlike participants who often align with beauty pageant ideals, Choi Hye-seon is portrayed as a multifaceted individual with notable achievements in bioinformatics and professional experience in Silicon Valley. This study analyzes her representation in Episodes 1 and 12 of Single's Inferno 3 as a case study to explore the evolving concept of the modern woman in contemporary media. Grounded in postmodern feminist theory, which critiques essentialist views of womanhood and emphasizes the diversity of women's experiences, this research examines how Choi Hye-seon disrupts conventional stereotypes of femininity. Using Multimodal Discourse Analysis (MDA), the study deconstructs the visual, verbal, and interactive elements contributing to her portrayal as an empowered, multi-dimensional figure. The findings reveal how Single's Inferno 3 constructs a narrative that aligns with shifting global perceptions of women's roles, positioning Choi Hye-seon as a symbol of the modern woman who navigates personal authenticity alongside intellectual and professional pursuits. This study contributes to the broader discourse on gender representation in reality television, highlighting how media can serve as a site for negotiating and redefining contemporary notions of womanhood in a globalized context.